Distal Femur Type III Open Fractures: Functional Outcome Analysis - Arul R Bhagyaraj; Anand Ashok; Manisha J Kumar; Krupakaran Ganesan; Anand Kurian; Dan B Inja; Manasseh Nithyananth; Vinoo M Cherian; Jeremy Bliss (Journal of Orthopedics and Joint Surgery)
Introduction: The common goal of open distal femoral fracture management is the restoration of bone alignment, soft tissue management, rotation, length, and stable fixation of the fracture and early mobilization. Open distal femur fractures are prone to complications such as knee stiffness and fracture-related infection. The decision of single-stage fixation or staged reconstruction is often multifactorial with a need to assess their impact through functional outcomes. Methods: Patients who underwent surgical fixation for open distal femoral fractures from January 2015 to December 2020 were included. Functional outcomes were documented using Schatzker and Lambert criteria scoring and the Oxford knee score on follow-up. A total of 30 out of 36 patients had underwent surgical fracture fixation at the time of presentation and 6 patients underwent transfemoral amputation. Results: AO33C3 was the major fracture type and was also associated with poorer functional outcomes (p-value of 0.037). About 11% of patients had vascular injuries, all of whom underwent amputation. The high velocity of injury correlated with poor knee range of movements (p-value of 0.030). The primary fixation group had 64% patients with excellent functional outcomes, whereas among those who underwent staged procedures, only 30% had excellent functional outcomes. During the course of treatment, 10 patients were diagnosed to have fracture-related infection. Early presentation and single staged definitive fixation within 24 hours with aggressive follow-up yielded nearly 60% excellent to good outcomes with 83% of the patients returning to some form of vocation, among whom, 55.55% returned to the same profession. There were 17 excellent, 2 good, 1 fair, and 9 poor outcomes in the mean follow-up period of 5.5 years. Conclusion: Type III open distal femur fractures are a challenging group to manage; however, with early debridement, primary definitive fixation, and aggressive follow-up, it is possible to achieve predictable and optimum outcomes.